Pathogenesis-Related Protein 1b1 (PR1b1) Is a Major Tomato Fruit Protein Responsive to Chilling Temperature and Upregulated in High Polyamine Transgenic Genotypes - Goyal, Ravinder K.; Fatima, Tahira; Topuz, Muhamet; Bernadec, Anne; Sicher, Richard; Handa, Avtar K.; Mattoo, Autar K. (Frontiers in Plant Science, 2016)
Plants execute an array of mechanisms in response to stress which include upregulation of defense-related proteins and changes in specific metabolites. Polyamines – putrescine (Put), spermidine (Spd) and spermine (Spm) - are metabolites commonly found associated with abiotic stresses such as chilling stress. We have generated two transgenic tomato lines (556HO and 579HO) that express yeast S-adenosylmethionine decarboxylase and specifically accumulate Spd and Spm in fruits in comparison to fruits from control (556AZ) fruit (Mehta et al., 2002). Tomato fruits undergo chilling injury at temperatures below 13 oC. The high Spd and Spm tomato together with the control azygous line were utilized to address role(s) of polyamines in chilling-injury signaling. Exposure to chilling temperature (2 oC) led to several-fold increase in the Put content in all the lines. Upon re-warming of the fruits at 20 oC, the levels of Spd and Spm increased further in the fruit of the two transgenic lines, the higher levels remaining stable for 15 days after re-warming as compared to the fruit from the control line. Profiling their steady state proteins before and after re-warming highlighted a protein of ~ 14 kD. Using proteomics approach, protein sequencing and immunoblotting, the ~ 14-kD protein was identified as the pathogenesis related protein 1b1 (PR1b1). The PR1b1 protein accumulated transiently in the control fruit whose level was barely detectable at d 15 post-warming while in the fruit from both the 665HO and 579HO transgenic lines PR1b1 abundance increased and remained stable till d 15 post warming. PR1b1 gene transcripts were found low in the control fruit with a visible accumulation only on d 15 post warming; however, in both the transgenic lines it accumulated and increased soon after rewarming being several-fold higher on day 2 while in 556HO line this increase continued until d 6 than the control fruit. The chilling-induced increase in PR1b1 protein seems independent of ethylene and methyl jasmonate signaling but may be linked to salicylic acid. We propose that polyamine-mediated sustained accumulation of PR1b1 protein in post-warmed chilled tomato fruit is a pre-emptive cold stress response and possibly a defense response mechanism related to